Effects of forest characteristics on the abundance of alectorioid lichens in northern Finland - Jaakkola, Lotta Maaria; Helle, Timo Päiviö; Soppela, Jussi; Kuitunen, Markku Tapio; Yrjönen, Mikko Juhani (Canadian Journal of Forest Research, 2006)
Quantitative knowledge of the abundance of epiphytic alectorioid lichens (Bryoria spp., Alectoria spp., and Usnea spp.) is important when evaluating the carrying capacity of the winter pastures of semidomesticated reindeer (Rangifer tarandus tarandus (L., 1758)) and woodland caribou (Rangifer tarandus caribou (Gmelin, 1788)). This study, including a total of 234 sample plots, presents data on the biomass of alectorioid lichens in mature forests for the most common forest site types in the national parks of Oulanka, Pallas-Ounastunturi, and Lemmenjoki in northern Finland and relates them to forest stand characteristics. The biomass of alectorioid lichens on trees was estimated using the clump method in which the existing clumps of lichen thalli on branches are compared with clumps of lichens of known dry mass. Estimated biomasses were corrected by equations describing the ratio of estimated to measured biomass. We found the highest mean lichen biomasses (120 kg·ha –1 ) in subdry, Scotch pine (Pinus sylvestris L.) dominated sites above the timberline of Norway spruce (Picea abies (L.) Karst.). Below that timberline, the highest lichen biomasses were found in fresh (productive) sites dominated by Norway spruce. There the site-specific differences were mainly associated with tree species composition. Though in many previous studies forest age has been an important indicator of total lichen biomass, in our study areas lichen abundance was most commonly correlated with total volume of forest stands. The correlation of biomass with forest volume suggests that substrate availability was the most important limiting factor for alectorioid lichens in our study area. However, it is premature to say whether that is a common feature in northern forests over larger geographic areas.